Influence of flake density and tempering on the feeding value of steam-flaked corn for feedlot cattle - B. H. Gutierrez (Journal of Applied Animal Research, 2018)
A feedlot growth-performance trial was conducted to evaluate the relative response to tempering when flake density (FD) of corn is increased from 0.31 kg/L (24 lb/bushel) to 0.39 kg/L (30 lb/bushel). Treatments were (1) non-tempered, FD = 0.31 kg/L; (2) non-tempered, FD = 0.39 kg/L; (3) tempered, FD = 0.31 kg/L and (4) tempered, FD = 0.39 kg/L. Tempering prior to flaking increased (21%, P < .01) the moisture content of corn as it exited the rolls and decreased (14%, P = .02) the starch enzymatic reactivity. Increasing roll tension to reduce FD decreased flake thickness (24%, P < .01) and increased starch reactivity (43%, P < .01). Increasing FD decreased (P = .03) estimated dietary NEm and NEg, and the estimated NEm and NEg values of steam-flaked corn by 2.3% and 2.9%, respectively. We conclude that whereas tempering corn grain before steam flaking increases the moisture content of corn as it exits the roles, it has minimal influence on the feeding value for corn for feedlot cattle. Increasing FD from 0.31 to 0.39 kg/L decreases starch reactivity and the net energy value of corn, but does not affect daily weight gain or carcass characteristics.